(untitled) (International Journal of Engineering and Computer Science, 2017)
Schemes like conventional password schemes such as textual password scheme, graphical scheme are commonly used for authentication. But these schemes are vulnerable to dictionary attack, shoulder surfing attack, accidental login. Hence the text-based shoulder surfing resistant graphical password schemes have been proposed. These existing schemes are not secure and efficient enough and have high failure rate. The text-based shoulder surfing resistant graphical password scheme is improved by using colors. In addition one time password is also used. So it has become more secure. User can easily login to the system. Unauthorized user cannot get the password easily. Hence this scheme provide protection against the shoulder surfing